Suppression of Glucagon-Like Peptide-1 Release by Inhibition of Intestinal NLRP3 Inflammasome Activation in Asc–/– and Nlrp3–/– Mice - Chen, Yu; Kidd, Jason; Bhat, Owais M.; Yuan, Xinxu; Hong, Jinni; He, Xingxiang; Li, Pin-Lan (Frontiers in Physiology, 2019)
The glucagon-like peptide-1 (GLP-1) is an insulinotropic hormone secreted by intestinal enteroendocrine L-cells, which plays a crucial role in glucose control, regulation and protection from different pathological conditions such as diabetes mellitus. The present study sought to test whether GLP-1 release increases gut injury with a high-fat diet (HFD) and whether this GLP-1 release is associated with NLRP3 inflammasome activation. Our results showed that the NLRP3 inflammasome is activated in the intestinal tissue of wild type mice on a HFD, accompanied by GLP-1 over-expression. The number of intestinal L-cells and the GLP-1 level in serum are increased in WT mice with HFD. However, in the Asc-/- and Nlrp3-/- mice these HFD-induced intestinal and serum GLP-1 changes was suppressed. Using confocal microscopy, the co-localization of GLP-1 and FLICA which labels activated caspase-1 in intestine was decreased in the Asc-/- and Nlrp3-/- mice compared to WT mice. Mechanistically, the inhibitor of caspase-1 or HMGB1 blocker is used to demonstrate the regulatory action of NRLP3 inflammasome in GLP-1 release. It was found that the level of GLP-1 and its co-localization with IL-1β were reduced by inhibition of the caspase-1 activity, but not altered by blockade of HMGB1 action. Our results suggest that NLRP3 inflammasome activation triggers GLP-1 production from the intestine, which is associated with IL-1β, but not with HMGB1. These findings for the first time provide evidence that the activation of NLRP3 inflammasome in the intestine increases GLP-1 release in mice, which may serve as an adaptive response to intestinal inflammation.